Job Burnout, Individual Coping Styles and Well-Being at Work: A Comparative Study of Men and Women Employees of a Private Enterprise - Sinha, Vinita (Prabandhan: Indian Journal of Management, 2010)
Burnout, a phenomenon that has been widely acknowledged as an important issue among people helping professionals, still lacks both precise theoretical foundations and substantial empirical support. Its conceptual and operational definitions vary widely. The broadcast definitions equate Burnout with stress, connect it with a long list of adverse health and well being variables and suggest that it is caused by relentless pursuit of success. Burnout has been related to human service professions with chronic inter-personal stress as its caused (Maslach and Jackson, 1981). It is conceived as a state of mental, physical and emotional exhaustion, typically occurring as a result of long-term involvement with people in situations, which are emotionally demanding. Burnout can be defined as the end result of stress experienced, but not properly coped with resulting in symptoms of exhaustion, irritation, ineffectiveness, discounting of self, others and problems of health (Hypertension, Ulcers and Heart Problems).